(untitled) (Far Western Review, 2025)
Being specific to socio-cultural dynamics, this study aims to explore and analyse the dynamics of students and interpret them in the context of remote school-level English language classrooms in Nepal. For this qualitative study, the research process was guided by narrative inquiry, and five secondary-level students (three males and two females) were selected as participants using a purposive sampling technique. As per the purpose, the information was drawn through in-depth interviews and personal conversations with the participants, followed by quality and ethical standards - authenticity, reflexivity, rapport building, privacy and anonymity of the participants and uttered narratives. As a result, the narratives were thermalized based on the identical perceptions and experiences. The finding shows that the classroom dynamics of the students in language classrooms are significantly influenced by socio-cultural dynamics – poor family and educational background, community and parental misconceptions, power imbalance, etc. As a result, such students experience language anxiety and shyness and perform silent behaviors, poor interaction, demotivation and disconnectedness in the classrooms. Being specific, this study may be meaningful to the students, language teachers, authors, policy makers, etc. Finally, being socio-cultural dynamics as a key determinant of classroom dynamics, it needs to be well-explored through different perspectives to expand its scope.